Stability control and turning algorithm of an alpine skiing robot - Kim, Si Hyun; Lee, Bumjoo; Hong, Young Dae (Sensors (Switzerland), 2019)
This paper proposes a general stability control method that uses the concept of zero-momentpoint (ZMP) and a turning algorithm with a light detection and ranging (LiDAR) sensor for a bipedal alpine skiing robot. There is no elaborate simulator for skiing robots since the snow has complicated characteristics, such as compression and melting. However, real experiments are laborious because of the many varied skiing conditions. The proposed skiing simulator could be used, so that a humanoid robot can track its desired turning radius by modeled forces that are similar to real ones in the snow. Subsequently, the robot will be able to pass through gates with LiDAR sensors. By using ZMP control, the robot can avoid falling down while tracking its desired path. The performance of the proposed stabilization method and autonomous turning algorithm are verified by a dynamics simulation software, Webots, and the simulation results are obtained while using the small humanoid robot platform DARwIn-OP.
Keywords: Complicated characteristics; Dynamics simulation; LIDAR sensors; Light detection and ranging; Small humanoid robots; Stability control; Stabilization methods; Turn radius; Navigation based on LIDAR sensor; Skiing robot; Stability control; Turn radius